Long-Lasting, Steady and Enhanced Energy Harvesting by Inserting a Conductive Layer into the Piezoelectric Polymer - Jang, Hak Su; Kim, Gwang Hyeon; Jeon, Dong Won; Park, Hyeon Jun; Bae, Bit Na; Alluri, Nagamalleswara Rao; Kim, Cheol Min; Baek, Changyeon; Lee, Min Ku; Cho, Sung Beom; Lee, Gyoung Ja; Park, Kwi Il (Advanced Functional Materials, 2025)
Flexibility, higher piezoelectric performance, and long-lasting stability of devices have a great demand in next generation energy technologies. Polyvinylidene fluoride (PVDF) polymer has a greater mechanical flexibility, but it suffers from low piezoelectric performance. Herein, sandwich-structured piezoelectric film (SS-PF) is designed by inserting the conductive poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) layer between two PVDF layers. The SS-PF based flexible piezoelectric energy harvester (f-PEH) generates higher voltage and current of 3.73 times and 4.64 times than the pristine PVDF film type f-PEH. Moreover, the SS-PF based f-PEH shows no degradation in the output voltage confirming the excellent long-lasting stability over 6 months. DFT simulation shows the occurrence of intermolecular forces between the PVDF/PEDOT:PSS interface. The electric field-dependent charges alignment in PEDOT:PSS may induce the charge accumulation at the PSS-PVDF interface and charge depletion at the PEDOT-PVDF interface leading to the change in orientation of molecular structure in PVDF. Next, the SS-PF based f-PEH is tested for a vibration sensor to monitor the vibrations of curvy pipes and machines, and its output voltages are comparable with the commercial PVDF vibration sensor to confirm the real-time use. The results present a novel design strategy, indicating a new direction for investigating piezo-polymer-based f-PEH.
Keywords: Ethylenedioxythiophenes; Interfacial polarization; Long lasting; Piezoelectric energy harvesters; Piezoelectric energy harvesting; Piezoelectric film; Polarization reversals; Poly(3,4-ethylenedioxythiophene) polystyrene sulphonate; Poly(styrene sulfonate); Polyvinylidene fluorides; interfacial polarization; PEDOT:PSS; piezoelectric energy harvesting; polarization reversal; PVDF